Necrotizing Skin Findings in Coronavirus Disease 2019: A Case Report - Fatmagul Kusku; Damlanur Sakiz (Iranian Society of Pathology, 2021)
Coronavirus is a single-stranded RNA virus that causes acute respiratory syndrome and various skin lesions. In addition, ischemic acral lesions have been reported in patients with severe coronavirus disease 2019 (COVID-19) due to coagulation disorders. We here present a case with ischemic acral lesions caused by COVID-19. The patient was 51-year old male who was hospitalized with COVID-19 pneumonia. After 28 days in the Intensive Care Unit, patient developed acroischemic lesions in the fingers and toes. In the histopathologic examination, vasculitis was observed as the infiltration of mixed-type inflammatory cells in the mid-sized muscular arteries wall. Moreover, microthrombosis was detected in small capillaries. It is clear that thrombotic lesions have occurred as a result of COVID-19 or administered treatment. Further studies are required to confirm and better characterize the skin reactions in COVID-19.